ANALISIS KETIDAKSANTUNAN BERBAHASA PADA KOLOM KOMENTAR YOUTUBE DEBAT CAWAPRES TAHUN 2024 DALAM CHANNEL NARASI - Muh. Khairul Nizam Rasmiah; Idris; Muhammad Idris (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
ABSTRACT This study aims to analyze the forms and contributing factors of impoliteness in comments posted on a YouTube video of the 2024 Vice Presidential Debate on the Narasi channel. The research employed a qualitative method with a pragmatic discourse analysis approach. Data were collected through documentation of comments over three months and analyzed using Jonathan Culpeper’s (1996) theory of impoliteness. The results show that the forms of impoliteness identified include bald-on-record, positive impoliteness, negative impoliteness, sarcasm, and withholding politeness. The most dominant type was positive impoliteness, expressed through subtle derision, followed by sarcasm, direct impoliteness, negative impoliteness, and avoidance strategies. Contributing factors include weak social ties, disregard for social hierarchy, and deliberate neglect of politeness norms in online interactions. This research highlights the need for greater awareness of digital communication ethics as part of digital literacy. The findings are expected to encourage more polite and constructive communication in virtual public spaces